The Concept of Subsistence in Classical Theory - Levine, D. (Journal of Income Distribution®, 1993)
This paper explores the concept of subsistence in the theories of Adam Smith, David Ricardo, Karl Marx and certain modern thinkers strongly influenced by their approaches. The different uses of the term subsistence in these theories are surveyed and assessed, and some implications of the differences n usage for important theoretical arguments are considered. The problem is examined of dividing consumption into different parts, one recalling the subsistence idea, the other going beyond subsistence. Also considered is the importance of the idea of a minimum level of consumption and level of life. The paper treats the classical idea critically but sympathetically, arguing that because the subsistence refers us to a level of need that ought to be significantly protected from the market, it raises enduring questions about the limits of the market as a means for providing people with the things they need.